Persistent atrial fibrillation ablation: conventional versus driver-guided strategy. (November 2015) - Lim, Han S; Sacher, Frédéric; Zellerhoff, Stephan; Jesel, Laurence; Shah, Ashok J; Komatsu, Yuki; Daly, Matthew; Denis, Arnaud; Derval, Nicolas; Hocini, Mélèze; Jaïs, Pierre; Haïssaguerre, Michel
While pulmonary vein isolation for paroxysmal atrial fibrillation (AF) is highly effective, catheter ablation for persistent AF remains a challenge with varying clinical success reported. Several ablation techniques have been proposed to target persistent AF, with the additional ablation of complex fractionated electrograms and linear lesions shown to provide incremental success to pulmonary vein isolation alone. Recently, several studies have suggested the presence of localized drivers (re-entrant or focal) in AF. By targeting these drivers, clinical outcomes may be maintained while minimizing the extent of ablation. This article will focus on the conventional stepwise ablation approach for persistent AF versus driver-guided ablation with the use of newer mapping technologies.